Peran Mahasiswa Kuliah Praktek dan Pengabdian Kepada Masyarakat Mahasiswa IAKN Tarutung Dalam Meningkatkan Kemampuan Calistung Anak Di SD Desa Pagar Batu - Adiani Hulu; Elen Veralija Pasaribu; Elisabeth Situmeang; Yoni Tika Mawati Zalukhu (Universitas Kristen Indonesia Toraja, 2024)
This research aims to evaluate the role of students in the Practical Lecture and Community Service (KPPM) program from the Tarutung State Christian Religion Institute (IAKN) to improve reading, writing and arithmetic skills (calistung. As well as to explore and analyze the role of students in practical and community service lectures to the community (kppm), in improving the calistung abilities of children in the village of Pagarbatu. In this journal, researchers will discuss the role of practical college students and community service in increasing calistung among children in the village of Pagarbatu. The results of the research show that KPPM students play a significant role in developing children's calistung skills at the Pagarbatu village elementary school. Apart from that, student involvement in community activities also contributes to strengthening social relations and community support for children's education. This research concludes that the KPPM program involving students can be an effective model in improving the quality of basic education in rural areas. The recommendation given is that there needs to be continued support from educational institutions and local governments to expand and deepen the positive impact of this program.